2016
DOI: 10.1016/j.celrep.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Kataegis Expression Signature in Breast Cancer Is Associated with Late Onset, Better Prognosis, and Higher HER2 Levels

Abstract: SUMMARY Kataegis is a mutational process observed in ~55% of breast tumors that results in hypermutation in localized genomic regions. Using whole-genome sequence data of 97 tumors, we examined the distribution of kataegis loci, showing that these somatic mutations are over-represented on chromosomes 8,17, and 22 and enriched in genic regions and active chromatin elements. We show that tumors harboring kataegis are associated with transcriptome-wide expression changes consistent with low invasive potential. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 46 publications
11
53
2
Order By: Relevance
“…Multiple studies have reported hypermutated genomic regions in several cancer types (Nik-Zainal et al 2012;Alexandrov et al 2013a;D'Antonio et al 2016). These genomic regions referred to as "Kataegis," presumed to be the result of aberrant activity of apolipoprotein B mRNA editing enzyme, catalytic polypeptidelike (APOBEC) cytidine deaminases, tend to be enriched in C > T and C > G substitutions occurring within TpCpN trinucleotide contexts (Lada et al 2012 Table S1; D' Antonio et al 2016).…”
Section: Visualizationmentioning
confidence: 99%
“…Multiple studies have reported hypermutated genomic regions in several cancer types (Nik-Zainal et al 2012;Alexandrov et al 2013a;D'Antonio et al 2016). These genomic regions referred to as "Kataegis," presumed to be the result of aberrant activity of apolipoprotein B mRNA editing enzyme, catalytic polypeptidelike (APOBEC) cytidine deaminases, tend to be enriched in C > T and C > G substitutions occurring within TpCpN trinucleotide contexts (Lada et al 2012 Table S1; D' Antonio et al 2016).…”
Section: Visualizationmentioning
confidence: 99%
“…Kataegis status, identified through an expression signature, has recently been shown to be associated with late onset, better prognosis and higher HER2 levels in breast cancer 45 . To further investigate the prognostic role of kataegis, a Cox regression was fit for overall survival between kataegic and kataegis-free patients, adjusting for age and sex for each cancer type (Supplementary Figure 18, Supplementary Table 11).…”
Section: Kataegismentioning
confidence: 99%
“…Chromoplexy is another catastrophic event characterized by chains of translocations resulting from punctuated bursts of interchromosomal SVs and CNAs (Baca et al 2013). Additional mutational processes include localized hypermutation involving small-scale alterations (sSNVs and indels) as in the case of kataegis, which is attributable to cytosine deam-ination catalyzed by AID/APOBEC proteins (Lada et al 2012;D'Antonio et al 2016). Impaired DNA mismatch repair (MMR) leading to microsatellite instability can also increase the rate of sSNVs and indels.…”
Section: Big Bang Tumor Growth and Clonal Evolutionmentioning
confidence: 99%